DEVELOPING MARKETING STRATEGY OF NASATECH KITCHEN SET MALANG TO ENTER A NEW MARKET IN USA - Dina Sagita Hartono; Josephine Christina Wiranto; Reynexy Gigih Aditama; Alhajeri Abdulrahman (AIBPM Publisher, 2018)
Nasatech is a company that produces kitchen cabinets from granite materials. Nasatech has been almost ten years in the city of Malang, Indonesia. So far, Nasatech only serve consumers who live in Malang and surrounding areas. However, Nasatech has a commitment to be able to market its products abroad if there is a chance. The excellence of Nasatech is its unique product and Nasatech has already used to use internet marketing to market its products and conduct online transactions. Some research data show that furniture and kitchen countertops from granite materials are becoming a trend in the US so Nasatech is very suitable to market its products in the US. Nasatech needs to make some patent designs for its products with knock-down system so it is more easily shipped and marketed to the US through furniture importers in the US who can become a distributor. Internet marketing can be a good marketing strategy to enter the US market as online furniture purchase transactions increase significantly in the US. This is expected to be a good opportunity for Nasatech to enter the US market.